Fort Rotterdam’s Contribution to The Development Of Cultural Heritage - Sri Rezky Meiliana, Sri Rezky Meiliana; Syukur, Syamzan; Mastanning (Al-Hikmah, 2023)
This research aims to examine the role of Fort Rotterdam as a cultural heritage development in people’s lives. This research is qualitative research using library research and field research. The steps in historical research are heuristics, source criticism, interpretation and historiography. The establishment of Fort Rotterdam was initiated by King Gowa IX Tumaparisi Kallonna as a royal defense base and continued by his son Karaeng Tunipalangga. The results of this research show that Fort Rotterdam continues to experience changes in function in each period. The role of Fort Rotterdam as a post-independence cultural heritage development in people’s lives can be seen in several aspects of society’s social, economic and political life. The role of Fort Rotterdam as a source of increasing understanding regarding history and culture, a means of building social relations, a means of maintaining the local identity of the Makassar community, and improving the community’s economy.